Development of a Model for the Establishment of a Hydro Electric Power Generating Plant - Oshin Ola Austin; Kabir A. Lasisi; Ajayi Joseph Adeniyi; Oluwasanmi Alonge (Journal La Multiapp, 2020)
Nigeria as a nation has suffered a lot when it comes to the availability of electricity. A clear comparison between this nation’s electric power supply and other countries revealed the present incessant electric power supply in the country. The average power per capital (watts per person) in the United States is 1,377 Watts. In Canada, it is as high as 1,704 Watts per person and in South Africa; it is 445 Watts per person. The average power per capital in Australia is 1,112 Watts and in New Zealand it is 1,020 W per person. Whereas, the average power per capital (watts per person) in Nigeria is 14 W person. The power system structure is characterized with a lot of faults and outages. These electric power problem has destroyed the industrial processes in the country. As a result, unemployment has increased in the country. As at February, 2020, according to the Federal Government of Nigeria, the number of unemployed youths in the country is 23 million. Data from the International Transparency in the United State stated that there are 40 million unemployed youths in the country. This has increased crime rates among the youths. The country experience a high level of hardship, insecurity and socio-economic disorder as results. Therefore, there is an urgent need to solve this incessant supply of electric power in the country. Hence, a detail study of Akure132/33kV substation Network of the Benin Electricity Distribution Company under which there are 84,264 customers was carried out.